Citrullination of CNS proteins in the pathogenesis of multiple sclerosis. (July 2011) - Bradford, Claire Margaret; Cross, Alison Kay; Haddock, Gail; Woodroofe, Nicola; Sharrack, Basil
Multiple sclerosis is a chronic immune-mediated disease of the CNS. Although it is a predominantly T-cell mediated condition, B cells and autoreactive antibodies play an important role in its pathogenesis, with the presence of oligoclonal immunoglobulins in the cerebrospinal fluid being an important diagnostic indicator. The target of these immunoglobulins has not yet been fully characterized. However, post-translational modifications of CNS-specific proteins are thought to contribute to their production through the generation of novel epitopes. One post-translational modification in particular, the conversion of the amino acid arginine to the nonstandard amino acid, citrulline, has been increasingly described in the literature as a factor in the pathogenesis of this condition. In this article, we summarize and discuss the current knowledge on citrullination in multiple sclerosis, the importance of this in relation to its pathogenesis and, potentially, its diagnosis.